"Combo" technique for the use of 7F guide catheter system during transradial approach. Issue 6 (10th August 2015) - Patel, Tejas; Shah, Sanjay; Pancholy, Samir
Abstract : Even a regular lumen of radial artery may create difficulty in smooth negotiation and propagation of a 7F guide catheter while performing intervention through transradial approach. We describe successive five cases of a simple and innovative "Combo" technique, which helps relatively atraumatic tracking of a 7F guide catheter through the course of arm and chest vasculature for successful completion of procedure without significant damage and local pain. © 2015 Wiley Periodicals, Inc.